Optimisasi Rute Penyelamatan Robot Mobil dalam Labirin: Algoritma Pencarian Jalur Terpendek - Wahyuni, Sri; Fuad, Muhammad; Umam, Khanif Khoirul; Sya’diyah, Lailatus; Laksono, Deni Tri (Rekayasa, 2025)
An area where a fire occurs is generally covered in smoke, hot air and dangerous for firefighters to enter. Robotics technology, especially mobile robots, makes it possible to be used as a rescuer to replace the role of the firefighter team. The task of the rescue mobile robot is to thoroughly explore the area and then on the next iteration, the mobile robot is able to find the shortest path by eliminating paths that lead to dead ends. The robot's ability to map and choose the shortest path is the goal of this research. The path is a black line intersecting at a 90° angle. The method applied to achieve the objectives in this research is the maze mapping algorithm left hand rule. The maze solving algorithm left hand rule method was chosen as a solution to plan the shortest path in a maze-shaped environment by creating codes such as L (Left), S (Straigh) and U (Dead End). After the codes were compiled from the mapping process, the code was simplified so that the robot could find a way out of the maze with the shortest path. The success rate was 90%, out of ten tests using the maze mapping left hand rule method, resulting in nine successes and one failure. The fastest mapping time was 23 seconds and the average was 62 seconds, while the shortest time was 8 seconds and the average was 27 seconds.